Factors Related to the Behavior of River Water Use in Bathing, Washing, and Toilet Activities in Tembilahan Hulu Village: Faktor – Faktor Yang Berhubungan Dengan Perilaku Penggunaan Air Sungai Dalam Kegiatan Mandi, Cuci, Kakus (MCK) Di Kelurahan Tembilahan Hulu - Winda Mayasari; Elmia Kursani; Nurlisis Nurlisis (Badnur Medisa Group, 2022)
Bathing, Washing, Latrine (MCK) is a community activity that has become a routine activity every day. The behavior of the community in using river water for MCK activities is a hereditary activity, due to limited facilities and using the river as an MCK. The purpose of this study is generally to determine the factors related to the behavior of river water use in MCK activities in Tembilahan Hulu Village in 2022. The research method used is quantitative with an observational analytical type with a cross sectional approach. This study used a non-probability sampling technique by means of a concecutive sampling technique. An interview was conducted for the distribution of questionnaires to 363 heads of families in Tembilahan Hulu Village in April-May 2022. The results showed that the factors related significantly to the behavior of river water use in MCK activities were knowledge (p value = 0.001, OR = 2.665) attitude (p value = 0.010, OR = 1.808) economic status (p value = 0.001, OR = 5.694) means (p value = 0.001, OR = 12.866) the role of health workers (p value = 0.006, OR = 1.890). From the results of the study, it can be concluded that the knowledge, attitudes, economic status, facilities, and role of health workers are risk factors for the use of river water in MCK activities in Tembilahan Hulu Village in 2022.